Insurance as a loan agreement for managing risk in corporate lending - Đekić Marija; Ristanović Vladimir (Trendovi u Poslovanju)
Credit risk management is one of the most important banking operations, both in developed and developing countries. In addition to numerous methods and techniques, banks decide to conclude special credit agreements when granting loans to economic entities. The special provisions of such an agreement provide additional assurance to the lender that it will not incur losses when borrowing funds. In these loan agreements, insurance plays a significant role, whether it is corporate or bank borrowing. In this paper, the subject of consideration is the role of insurance as a loan agreement in corporate lending primarily by banks. The aim of this paper is to describe the importance and role of insurance in the process of corporate lending, point out the benefits of the existence of provisions related to insurance in the loan agreement for both lender and borrower, and provide a brief overview of the use of insurance as a method of credit risk management, referring to the use of this type of agreement in Serbia as well.